PENGARUH PENGAWASAN PIMPINAN DAN KEBIJAKAN WORK FROM HOME TERHADAP KINERJA PEGAWAI PADA MASA PANDEMI COVID-19 DI BALAI PENGEMBANGAN KOMPETENSI PUPR WILAYAH V YOGYAKARTA - ARY SUBIYANTORO; Wahyudiyono Wahyudiyono; Himawan Agung Nugroho; Sri Wahyuning; Wini Angraeni (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this paper is to determine the effects of supervisory leadership and work from home policies on employee performance during the COVID-19 pandemic at the Regional V Public Works and Housing Competency Development Center Yogyakarta. This writing uses quantitative method. The population used is the staff of the Regional Public Works and Housing Competency Development Center V Yogyakarta. The sampling technique used is Non Probability Sampling. The number of samples is 32. Based on the results of the discussion, it is found that the T observed for leadership supervision is 2.546 > T table 2.048 and the work from home policy of T observed is 3.347 > T table 2.048. This has a partial effect on employee performance. The variable of leadership supervision and work from home policy have a simultaneous effect on employee performance based on the amount of F Test 16,852 > F table 3,33. The contribution of R2 has a strong relationship between leadership supervision and work from home policies in influencing employee performance, which is 0.538 or 53.8%.